Restructuring Emotive Behavior Therapy Untuk Meningkatkan Regulasi Emosi Pada Remaja Yang Mengalami Toxic Relationship - Azmatun Sholikha; Thalia Endang Wulandhani; Selma Larefa Mahabbah; Rajwa Satrio Haq; Muhammad Rofiqul Rahman (STKIP PGRI SUMENEP, 2025)
This study aims to explore the effectiveness of Restructuring Emotive Behavior Therapy (REBT) in improving emotional regulation in adolescents experiencing toxic relationships. The subject of the study was a 20-year-old male who faced emotional conflict due to an unhealthy romantic relationship and complex family problems, such as parental divorce and social stigma. This study uses a qualitative method. The research design used is a single-subject design (N = 1) with a pre-test, post-test, with follow-up (PPF) design to determine the effect of the intervention given on the emergence of angry emotions and the ability to regulate emotions. The population in this study were late adolescents in Cirebon Regency who had low Emotional Regulation. The sampling technique used in this study was purposive sampling. The research sample taken was a late adolescent who experienced a toxic relationship and had low emotional regulation, which was measured using the emotional regulation scale. The intervention used the REBT approach based on the ABCDE model (Activating Event, Beliefs, Consequences, Disputation, Effect). The results showed a significant increase in the subject's emotional regulation ability, including reduced maladaptive behaviors such as alcohol consumption and emotional outbursts. The subject also showed increased social interaction and healthier coping mechanisms, allowing for better interpersonal relationships and higher emotional stability. This study emphasizes the importance of emotional regulation training for adolescents in dealing with interpersonal conflicts, and recommends REBT as an effective therapeutic approach for similar cases in the future. Keyword: Restructuring Emotive Behavior Therapy, Emotional Regulation